Pengaruh Model Pembelajaran Multiliterasi Terhadap Hasil Belajar Siswa Pada Pembelajaran Bahasa Indonesia di SDN 112271 Siamporik - Windari, Salsabila; Sapri, Sapri; Siregar, Lailatun Nur Kamalia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the effect of the multiliteracy learning model on student learning outcomes in Indonesian language learning at SDN 112271 Siamporik. This research is quantitative research. The population used in this research were all class V students at SDN 112271 Siamporik, Kualauh Selatan District, North Labuhanbatu Regency, namely 40 students. The sampling technique in this research is using Non Probability Sampling with a total sampling method. Based on the results of hypothesis testing using the paired sample t test, it is known that the tailed sig-2 value is 0.024 in the control class and the tailed sig-2 value in the experimental class is 0.002, this value is <0.05 (significant level) therefore In this research, there is a difference in the average student learning outcomes for the Control Class Pre-Test and the Control Class Post-Test and there is also a difference in the average student learning outcomes for the Experimental Class Pre-Test and the Experimental Class Post-Test and based on the results of independent testing sample t test, it is known that the 2-tailed significant value is 0.000 and this value is (0.000) < 0.05, so it can be concluded that there is a difference in the average student learning outcomes between the learning model and the conventional model (other than the multiliteracy learning model) and from the table in The above also shows that the average Post-Test score for the Experimental Class (multiliteracy learning model) compared to the Post-Test score for the Control Class (Conventional) has increased, so it can also be concluded that the multiliteracy learning model is more effective in student learning outcomes in Indonesian language learning. rather than conventional learning models (apart from multiliteracy learning models).